Insertion and/or deletion of many repeated DNA sequences in human and higher ape evolution. - Hwu, H R (1986)
The total numbers of copies of two repeat families, L1 (Kpn I) and Alu, have been measured in the DNA of four higher apes by an accurate titration method. The number of members of the Alu family repeats in the four genomes are as follows: human, 910,000; chimpanzee, 330,000; gorilla, 410,000; orangutan, 580,000. For the Kpn I family (3'-ward higher frequency region) the number of copies in these genomes are as follows: human, 107,000; chimpanzee, 51,000; gorilla, 64,000; orangutan, 84,000. Thermal stability measurements show that, although the families of repeats are moderately divergent in sequence, little net sequence change has occurred during the evolution of the higher apes. Most or all of the members of these families of repeats are interspersed throughout the genome. Therefore, a large number of events of insertion and/or deletion of these DNA sequences has occurred during higher primate evolution.